THE ROLE OF INNOVATIVE TECHNOLOGIES AND INFORMATION COMMUNICATION TECHNOLOGIES IN IMPROVING THE QUALITY OF EDUCATION - Yuldasheva Shohista Tojaliyeva (Galaxy International Interdisciplinary Research Journal, 2021)
It should be borne in mind that the changes taking place in our society in the economic, social, political and cultural spheres also depend on the education system, which determines the intellectual potential of our country in the future and is a key condition for its development. At the same time, the growth of intellectual potential, the development of quality will not only increase the effectiveness of education, improve the system in this area, but also significantly affect the growth of all areas of this social system. That is why one of the strategic directions in education today is the identification of innovative activities of educational institutions as a key factor. This article discusses the role of innovative technologies and information and communication technologies in improving the quality of education.